ANALISIS IMPLEMENTASI MODEL EXPERIENTIAL LEARNING DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MATERI IBADAH PRAKTIS DI MAS - Latief Wahyu Pranoto; Subandi Subandi; Ais Isti’ana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning Islamic Religious Education on practical worship materials, especially funeral arrangements, requires understanding that is not only theoretical, but also applicable through direct experience. This study aims to analyze the implementation of the experiential learning model in improving students' understanding of funeral arrangements material at MAS Baitul Kirom. This study uses a qualitative approach with a descriptive design. The research subjects include Islamic Religious Education teachers and Madrasah Aliyah students. Data collection was carried out through observation, interviews, and documentation, while data analysis was carried out inductively through the stages of data reduction, data presentation, and drawing conclusions, and its validity was tested by triangulation of sources and methods. The results of the study indicate that the experiential learning model is applied systematically through four stages, namely concrete experience, reflective observation, abstract conceptualization, and active experimentation. The implementation of this model provides a meaningful learning experience and contributes positively to students' understanding in the cognitive, affective, and psychomotor aspects. Overall, student understanding was in the good category, with an average class score of 82, and 79% of students achieving the Minimum Completion Criteria. Thus, the experiential learning model has proven relevant and effective in improving student understanding of practical worship materials on funeral arrangements and can be used as an alternative contextual and applicable Islamic Religious Education learning model.